2012
DOI: 10.1088/0004-637x/758/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Point Shock and Flux Rope Analysis of Multiple Interplanetary Coronal Mass Ejections Around 2010 August 1 in the Inner Heliosphere

Abstract: We present multi-point in situ observations of a complex sequence of coronal mass ejections (CMEs) which may serve as a benchmark event for numerical and empirical space weather prediction models. On 2010 August 1, instruments on various space missions (Solar Dynamics Observatory/ Solar and Heliospheric Observatory/Solar-TErrestrial-RElations-Observatory) monitored several CMEs originating within tens of degrees from solar disk center. We compare their imprints on four widely separated locations, spanning 120 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 96 publications
8
104
0
Order By: Relevance
“…So far, the largest number of spacecraft crossings remains the event of January 1978 with five spacecraft crossings. Burlaga et al (1981) deduced a general shape for the shock and the MC axis, which are still the expected typical shapes nowadays (Möstl et al 2012;Janvier et al 2013). Berdichevsky et al (2009) reanalyzed the same event and concluded that there was a strong speed gradient in longitude with a stronger speed around the apex than on the flanks of the shock.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…So far, the largest number of spacecraft crossings remains the event of January 1978 with five spacecraft crossings. Burlaga et al (1981) deduced a general shape for the shock and the MC axis, which are still the expected typical shapes nowadays (Möstl et al 2012;Janvier et al 2013). Berdichevsky et al (2009) reanalyzed the same event and concluded that there was a strong speed gradient in longitude with a stronger speed around the apex than on the flanks of the shock.…”
Section: Introductionmentioning
confidence: 79%
“…This provides an implicit constraint on the mean longitudinal extension of ICME shocks. Next, a limited sample of ICMEs have been analyzed by the STEREO twin spacecraft associated to other spacecraft, such as ACE, MESSENGER, VEX, or Wind (Kilpua et al 2011;Farrugia et al 2011;Möstl et al 2012). These studies provide constraints on the spatial extension and geometry of shocks in specific events.…”
Section: Introductionmentioning
confidence: 99%
“…When propagating into the solar wind, sympathetic events are prone to CME-CME interaction (e.g., Lugaz et al 2008Lugaz et al , 2012Liu et al 2014b). Such interactions may significantly modify the structure of the CME-driven shock wave and the properties of the interplanetary CME (ICME), and therefore affect the potential of space weather effects (e.g., Liu et al 2012Liu et al , 2014aMöstl et al 2012). Interactions between CMEs from the same AR have often been discussed (e.g., Lugaz et al 2005bLugaz et al , 2007Lugaz et al , 2013Xiong et al 2006), but CMEs can be spatially extended and those from distant regions may also interact, adding complexity to solar wind data (e.g., Temmer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such a distortion occurs over a relatively short heliocentric distance. Interactions between multiple CMEs have been revealed by in situ observations (e.g., Burlaga et al 1987;Wang et al 2003;Steed et al 2011;Möstl et al 2012), radio burst observations (e.g., Gopalswamy et al 2001;Oliveros et al 2012), white light (WL) imaging (e.g., Harrison et al 2012;Liu et al 2012;Lugaz et al 2012;Temmer et al 2012;Shen et al 2012a;Bemporad et al 2012), and numerical magnetohydrodynamic (MHD) simulations (e.g., Lugaz et al 2005;Xiong et al 2007Xiong et al , 2009; Shen et al 2012b). …”
Section: The Inner Heliospherementioning
confidence: 99%